Identifying Project Factors That Affect an Investor's Escalation of Commitment in Public-Private Partnership Projects. Issue 6 (December 2019) - Liu, Jiaqi; Liu, Jicai; Gao, Ruolan; Gao, Huaizhu Oliver; Li, Yahui
The study comprehensively discusses 18 project factors affecting investors' escalation of commitment (EOC) in a public-private partnership (PPP) project. Using factor analysis, five factor groupings were addressed: the project information and economic benefit, the reward and punishment mechanisms, project uncertainty, the degree of participation and completeness, and the resources invested in the project. The results revealed that the influence of five grouping factors on investor's EOC is not independent; after performing the weight analysis, the 18 factors had different influences on EOC. These findings offer effective suggestions and theoretical guidelines for reducing the risk of investor EOC.